The role of green finance in reducing agricultural non-point source pollution—an empirical analysis from China - Lv, Wen; Zhang, Zheng; Zhang, Xiaran (Frontiers in Sustainable Food Systems, 2023)
Introduction Green finance plays a crucial role in driving sustainable development and has the potential to effectively reduce pollution emissions, thereby positively impacting the environment. However, in the agricultural sector, China, unlike developed countries, primarily relies on a small-peasant economy, and the green financial system is not well-developed. As a result, the specific emission reduction effects and mechanisms of green finance on agricultural non-point source pollution (ANSP) remain unclear. The objective of our research is to explore the internal mechanisms through which green finance influences ANSP, with the aim of providing valuable policy insights to the government and promoting the green transformation of agriculture for enhanced food security. Methods This study employs an empirical analysis of green finance on ANSP using provincial panel data from China spanning the years 2005 to 2020. By utilizing robust data and applying empirical analysis, we can derive scientifically credible conclusions. We introduce a relative indicator to assess the trend of ANSP and investigate the pathways through which green finance operates using heterogeneity analysis, intermediary effect evaluation, and threshold effect analysis. Results and Discussion The empirical findings reveal the following insights: (1) While green finance demonstrates a significant reduction effect on ANSP, this effect varies across different regions. Specifically, the impact of green finance on ANSP reduction is more pronounced in areas characterized by strong comprehensive agricultural strength, high levels of economic development, and predominantly focused on plantation agriculture. (2) From a mechanistic standpoint, green finance substantially diminishes ANSP by facilitating agricultural scaling and promoting the adoption of green technologies. (3) The threshold effect analysis demonstrates that the mitigation effect of green finance on ANSP exhibits non-linear characteristics, with a double threshold effect observed. As the level of green finance development increases, the mitigation effect is further enhanced. Conclusion In conclusion, the appropriate implementation of green finance can effectively enhance the agricultural environment and ensure food security. Considering the heterogeneity of the role of green finance and the presence of threshold values, it is crucial for the government to tailor green finance policies according to local conditions. This research not only expands on previous studies but also offers valuable insights for the government in formulating green finance policies. Furthermore, it provides a viable pathway for reducing ANSP while serving as a reference for other developing countries aiming to establish green agriculture and sustain food system security.